Impact of low-grade inflammation on neurological outcomes in patients with acute pontine infarction: a retrospective cohort study - Zhu, Junyu; Zhou, Hai; Mo, Jierong; Zhou, Tianen; Jiang, Jun; Zhang, Zhiwen (Frontiers in Immunology, 2026)
BackgroundAcute pontine infarction significantly impacts neurological function and prognosis. Recent studies suggest that low-grade inflammation (LGI) may play a critical role in influencing recovery outcomes. However, the relationship between LGI and neurological prognosis in acute pontine infarction remains underexplored.ObjectivesThis study aims to investigate the correlation between LGI and neurological outcomes in patients with acute pontine infarction over 90 days post-stroke.MethodsA retrospective cohort study was conducted involving 502 patients diagnosed with acute pontine infarction at The First People’s Hospital of Foshan between January 1, 2015, and July 14, 2022. Clinical data, inflammatory markers (CRP, WBC, NLR, PLT), and neurological function assessed via NIHSS scores were collected and analyzed.ResultsElevated levels of inflammatory markers were significantly associated with poorer neurological outcomes. The LGI scores correlated positively with NIHSS scores at discharge and 90 days post-stroke, indicating that higher LGI is predictive of impaired recovery.ConclusionThis study demonstrates that low-grade inflammation is an important predictor of neurological outcomes in acute pontine infarction patients. Incorporating LGI assessments into clinical practice may enhance prognostic accuracy and inform treatment strategies.